Usability Analysis of Atma Jaya Catholic University E-Learning Based on Human Computer Interaction - Henoch Juli Christanto; Stephen Aprius Sutresno; Vincentius Setiawan Suandi (Journal of Information System and Informatics, 2023)
E-learning UAJ is a system provided by Unika Atma Jaya to facilitate the learning process for both students and lecturers. However, this system is still rarely used, especially among engineering faculties. This forms the basis for conducting the following analysis. The purpose of this research is to measure the level of usability of the UAJ e-learning system. Usability analysis is carried out using five components of usability outlined by Jakob Nielsen: Learnability, Efficiency, Memorability, Errors, and Satisfaction. The indicators within these five components are then compiled into a questionnaire, which will be distributed to active lecturers and students across all faculties who utilize the UAJ e-learning platform. This study employs a Likert scale with five categories, ranging from category 1 indicating "very bad" to category 5 indicating "very good." Among the five usability criteria assessed for both students and lecturers, the majority of responses fell within category 3, indicating sufficiency. The average scores ranged from 14.122 to 18.731 for lecturers and from 19.825 to 21.845 for students. Overall, the usability level of the UAJ e-learning platform is deemed satisfactory, enabling more effective utilization by both lecturers and students. Additionally, the study results propose several solutions for enhancing the development of the UAJ e-learning system.